Changes in global trade patterns and women's employment in manufacturing: An analysis over the period of Asianization and de-industrialization - Burça Kızılırmak; Emel Memiş; Şirin Saraçoğlu; Ebru Voyvoda (Turkish Economic Association, 2014)
The purpose of this study is to explore the employment effects of changes in manufacturing output resulting from changes in trade patterns over the period 1995-2006. For 30 countries (21 OECD and 9 non-OECD countries) we estimate the changes in embodied labor content due to trade using the factor-content analysis by breaking up the sources of these changes between the trade with the North, the South and China. We also decompose changes in employment into its components as changes within and across sectors. Our results present a net negative impact of trade on total employment in 30 countries over the period of analysis (despite employment gains in 17 countries). In all countries (except for Philippines and Republic of Korea) trade with China has a negative impact on total employment with a stronger negative effect on women's employment. Employment losses in the South due to surge in imports from China are coupled with declining exports to the North as many countries in the North shift their imports to emerging economies in Asia. Decomposition results indicate that decline in the share of women's employment is mainly due to shifts between sectors rather than within sector changes. Changes in women's employment are still highly dependent on the movements in 'traditional' manufacturing sectors including food, textiles and wearing apparel.
Keywords: F16; J16; J21; 330; North-South trade; decomposition analysis; factor content analysis; gender bias